Eucalyptus Bark Charcoal: the Influence of Carbonization Temperature in Thermal Behavior - Durango Padilla, Elias Ricardo [UNESP]; Oliveira Santos, Luis Ricardo; Silva, Diego Aleixo da; Barros, Joao Lucio de; Belini, Gabriela Bertoni; Yamaji, Fabio Minoru; Souza, Teofilo Miguel de [UNESP]; Campos, Cristiane Inacio de [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2019)
Eucalyptus bark is a waste generated in large volume and has been used as a source of energy. This study tries to use the Eucalyptus sp. bark as a source of raw material for the charcoal production and to study the influence of pyrolysis temperatures on charcoal properties. Charcoal was produced at different temperatures: 300, 400 and 500 degrees C, and their properties were determined by proximate analysis, higher heating value and thermogravimetric analysis. It was observed that higher pyrolysis temperature resulted in increase of the fixed carbon content and higher heating value. In the thermogravimetry and derivative thermogravimetry curves it was possible to determine the differences in the thermal stability of charcoal produced. It can be concluded that the eucalyptus bark charcoal is an alternative for the energy reutilization of this waste and also can be used as charcoal for heating.
Keywords: TGA; Biomass energy; Wood residue; Solid Biofuel